2018
DOI: 10.1016/j.jbi.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, cluster-based analysis of the electronic medical record of sepsis with composite mixture models

Abstract: The widespread adoption of electronic medical records (EMRs) in healthcare has provided vast new amounts of data for statistical machine learning researchers in their efforts to model and predict patient health status, potentially enabling novel advances in treatment. In the case of sepsis, a debilitating, dysregulated host response to infection, extracting subtle, uncataloged clinical phenotypes from the EMR with statistical machine learning methods has the potential to impact patient diagnosis and treatment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…This study also attempted to stratify the sepsis syndrome to advance the fundamental understanding of the progression of this disease (199). Several other groups have demonstrated the validity of such algorithms in retrospective studies (204)(205)(206). However, only a few machine learning-based algorithms have been implemented in prospective studies beyond the development phase using retrospective chart review.…”
Section: Beyond Rule-based Decision Support: Power Of Electronic Medimentioning
confidence: 99%
“…This study also attempted to stratify the sepsis syndrome to advance the fundamental understanding of the progression of this disease (199). Several other groups have demonstrated the validity of such algorithms in retrospective studies (204)(205)(206). However, only a few machine learning-based algorithms have been implemented in prospective studies beyond the development phase using retrospective chart review.…”
Section: Beyond Rule-based Decision Support: Power Of Electronic Medimentioning
confidence: 99%
“…Sepsis has been found to be consisted of several phenotypes, though specific class membership assignments are different across studies [12][13][14][15][16][17][18]. By using clinical trial data from 1696 patients, Gårdlund B and colleagues identified six classes of septic shock [19].…”
Section: Introductionmentioning
confidence: 99%
“…1). Three studies used an unsupervised clustering approach for clustering sepsis patients [31,42,44]. Data from sepsis patients were also used to learn optimal treatment by reinforcement learning [19].…”
Section: Machine Learning Techniques In Usementioning
confidence: 99%
“…In contrast to supervised ML models, unsupervised approaches for cluster analysis were used by only three studies identified in our review [31,42]. All three focused on sepsis patients.…”
Section: Outcome and Data Complexitymentioning
confidence: 99%
See 1 more Smart Citation